Pudendal nerve block in hemorrhoid surgery: A systematic review and meta-analysis. (28th May 2021) - Mongelli, F; Treglia, G; La Regina, D; Di Giuseppe, M; Galafassi, J; Majno-Hurst, P; Christoforidis, D
Abstract: Objective: Postoperative pain represents an important issue in traditional hemorrhoidectomy. Optimal pain control is mandatory, in particular in a surgical day care setting. The aim of this study was to investigate the use of pudendal nerve block (PNB) in patients undergoing hemorrhoidectomy. Methods: PubMed, Google Scholar, Cochrane Library and Web of Science databases were searched up to December 2020. Randomized trials evaluating the PNB use on postoperative outcomes in patients undergoing hemorrhoidectomy were selected. Opioid consumption, pain on the visual analogue scale, length of hospital stay and readmission rate were the main outcomes of interest and were plotted by using a random-effect model. Results: The literature search revealed 749 articles, of which 14 with were deemed eligible. A total of 1, 214 patients was included, of whom 565 received the PNB and 649 did not. After hemorrhoidectomy, patients in the PNB group received opioids less frequently (RR 0.364, 95%CI 0.292 to 0.454, p < 0.001) and in a lower cumulative dose (SMD -0.935, 95%CI -1.280 to -0.591, p < 0.001). Patients receiving PNB experienced less pain at 24 hours (SMD -1.862, 95%CI -2.495 to -1.228, p < 0.001), had a shorter length of hospital stay (SMD -0.742, 95%CI -1.145 to -0.338, p < 0.001) and a lower readmission rate (RR 0.239, 95%CI 0.062 to 0.916, p = 0.037). Sensitivity analysis excluded the occurrence of publication bias on the primary endpoint and the overall evidence quality was judged "high". Conclusion: This systematic review and meta-analysis shows significant advantages of the PNB use. A reduction in opioid consumption, postoperative pain, complications and length of stay can be demonstrated. Despite limitations, PNB in patients undergoing hemorrhoidectomy should be taken into account.